2005
DOI: 10.1007/s11258-005-0200-z
|View full text |Cite
|
Sign up to set email alerts
|

Recovery after Experimental Cutting and Burning in Three Shrub Communities with Different Dominant Species

Abstract: The aim of this study is to compare the recovery dynamics in three shrub communities subjected to experimental burning and cutting, and situated on an altitudinal gradient. Climatic features are different in each area, but all had the common characteristic of very homogeneous vegetation cover before the disturbances, with only one shrub species clearly dominant, a different taxon in each area, and with different regeneration strategies. The first area was a heathland dominated by Calluna vulgaris, situated at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
59
2
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(72 citation statements)
references
References 34 publications
10
59
2
1
Order By: Relevance
“…In the study area, 2 years after the fire, very good regeneration was observed in woody species such as E. australis and C. tridentatum, both of which are typical resprouters , and in seeders such as H. alyssoides. The cover values for these woody species increase significantly over time, a characteristic which has been widely documented in post-fire regeneration in shrublands with similar species composition (Calvo et al , 2005. Consequently, as described in other studies, an increase in woody species in the understorey is negatively correlated with pine seedling density in sites where density is very high (S1 and S3) and cover values for woody species are highest after 3 years (95% cover in S1 and 86% in S3).…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…In the study area, 2 years after the fire, very good regeneration was observed in woody species such as E. australis and C. tridentatum, both of which are typical resprouters , and in seeders such as H. alyssoides. The cover values for these woody species increase significantly over time, a characteristic which has been widely documented in post-fire regeneration in shrublands with similar species composition (Calvo et al , 2005. Consequently, as described in other studies, an increase in woody species in the understorey is negatively correlated with pine seedling density in sites where density is very high (S1 and S3) and cover values for woody species are highest after 3 years (95% cover in S1 and 86% in S3).…”
Section: Discussionsupporting
confidence: 69%
“…Fire creates open areas, which favour the germination of species by removing established vegetation, and also has direct effects on germination and seedling survival (Hanley and Fenner 1998). The passage of fire may facilitate germination and the development of several species by changing the mineral nutrient content of the environment (Marcos 1997;Calvo et al 2003Calvo et al , 2005. Trends in secondary succession beginning after a fire depend on several factors, including species composition in the initial community, fire severity, the season in which burning occurs (Dominguez et al 2002) and the existence of either a soil or aerial seed bank able to survive disturbances (Ferrandis et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with the general knowledge on different growth patterns between resprouters and non-resprouters. Non-resprouters begin flowering earlier and more abundantly after disturbance (Pate et al 1990, Bond & Van Wilgen 1996, allowing a faster colonization of suitable microhabitats as compared to resprouting species, whose regrowth from established root systems is restricted to microsites previously occupied (Keeley & Zedler 1978, Calvo et al 2005. Moreover, resprouters need more energy and time to regenerate after disturbance, due to their resource allocation to the replacement of damage tissues (Bond & Van Wilgen 1996, Arnan et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that both stand's biometric factors and climate affect the shrub growth rate (Calvo et al 2005, Castro & Freitas 2009. Hence, all available variables (i.e., shrub, stand and location variables) were tested as possible effects on growth rate (parameter b).…”
Section: Model Fitting and Selectionmentioning
confidence: 99%